2019
DOI: 10.1038/s41586-019-1086-6
|View full text |Cite
|
Sign up to set email alerts
|

Needle-like structures discovered on positively charged lightning branches

Abstract: The lightning flashes used in this work were mapped using data from the LO-FAR (LOw Frequency ARray) radio telescope. Due to its effective lightning protection system, LOFAR is able to continue to operate during thunderstorm activity[1]. The Dutch LOFAR stations consist of 38 (24 core + 14 remote) stations spread over 3200 km 2 in the northern Netherlands. The largest baseline between core stations is about 3 km, the largest baseline between remote stations is about 100 km. From each station we use 6 dual-pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
188
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(230 citation statements)
references
References 31 publications
32
188
9
1
Order By: Relevance
“…Combing all clues from the above analysis, we find that a mechanism described by Hare et al () in their supplementary material regarding line charge density redistribution of a leader channel with a two‐layer charge structure is more consistent with our observations than the leader‐disconnection mechanism. As shown in Figure , a positive leader is propagating leftward due to the ambient electric field.…”
Section: Discussion and Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Combing all clues from the above analysis, we find that a mechanism described by Hare et al () in their supplementary material regarding line charge density redistribution of a leader channel with a two‐layer charge structure is more consistent with our observations than the leader‐disconnection mechanism. As shown in Figure , a positive leader is propagating leftward due to the ambient electric field.…”
Section: Discussion and Analysissupporting
confidence: 89%
“…A nearby bidirectional leader initiated approximately 500 m from the preexisting positive leader that suppressed nearby needles, induced new flickers, created a disconnection on the main positive channel, and resulted in the needle extinguishment behind the disconnection. All these rarely observed yet perhaps common lightning processes and their interactions were analyzed and shown fundamentally consistent with a mechanism described by Hare et al () regarding a two‐layer leader charge structure, providing a new picture of needle and leader dynamics as summarized in Figure . Note that all results are derived from only one lightning flash, more observations are needed to validate these findings.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It has been suggested that the negative differential resistance behavior of lightning channels plays an important role in the mechanism of current cutoff, which in its turn makes some flashes transfer charge to ground by a series of (discrete) return strokes, while others by a single stroke followed by a long continuing current (Krehbiel et al, 1979;Hare et al, 2019;Heckman, 1992;Mazur et al, 1995). Recent review articles argue that the role of negative differential resistance in the channel cutoff remains to be quantified (Mazur & Ruhnke, 2014;Williams, 2006;Williams & Heckman, 2012;Williams & Montanyà, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of the steady-state resistance of arc channels has been used to discuss the phenomenology of lightning channels (Hare et al, 2019;Heckman, 1992;Krehbiel et al, 1979;Mazur & Ruhnke, 2014;Williams, 2006;Williams & Heckman, 2012;Williams & Montanyà, 2019). Steady-state plasma arcs exhibit the so-called negative differential resistance, that is, the resistance decreases with increasing electrical current.…”
Section: Steady-state Negative Differential Resistancementioning
confidence: 99%